2015
DOI: 10.1016/j.homp.2015.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tarantula cubensis D6 on aflatoxin-induced injury in biochemical parameters in rats

Abstract: Our results indicated that Tarantula cubensis D6 partially neutralized the deleterious effects of aflatoxin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 40 publications
4
15
0
Order By: Relevance
“…In fact, our results show how prolonged exposure to AFB1 is related to a significant increase in oxidative stress; in particular, the brain tissue of mice exposed to AFB1 (750 µg/kg orally every three days for 46 days) showed a significant increase in lipid peroxidation and also an impairment in those endogenous systems responsible for endogenous antioxidant defense such as GSH, SOD and CAT. Our results are therefore in line with other studies that have also demonstrated the induction of oxidative stress in the brains and livers of rodents that were subjected to different schemes of AFB1 administration [56,57]. GSH, catalyzed by GST and conjugated with AFB1, is considered the most important detoxification reaction to protect both the liver and extrahepatic tissues from AFB1 toxicity [58,59].…”
Section: Discussionsupporting
confidence: 92%
“…In fact, our results show how prolonged exposure to AFB1 is related to a significant increase in oxidative stress; in particular, the brain tissue of mice exposed to AFB1 (750 µg/kg orally every three days for 46 days) showed a significant increase in lipid peroxidation and also an impairment in those endogenous systems responsible for endogenous antioxidant defense such as GSH, SOD and CAT. Our results are therefore in line with other studies that have also demonstrated the induction of oxidative stress in the brains and livers of rodents that were subjected to different schemes of AFB1 administration [56,57]. GSH, catalyzed by GST and conjugated with AFB1, is considered the most important detoxification reaction to protect both the liver and extrahepatic tissues from AFB1 toxicity [58,59].…”
Section: Discussionsupporting
confidence: 92%
“…The relationship of ALT elevation and AFB1 and vice versa can also be supported through considering the early work of Thaxton and Hamilton (18) and Gawai et al (19) in which the proved the elevation of ALT, as indication of acute liver injury, in birds that had been given a single dose of aflatoxin compared to control untreated birds. The reported increase of ALT in AFB1 positive patients can also find support in more recent studies which demonstrate the significant increase of ALT among other biochemical parameters in rats fed AFB1 (20)(21)(22). Therefore this study exhibits similarity to the previously research which prove that AFB1-induced liver injury can be attributed to the oxidative stress.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the contents of H 2 O 2 , MDA and LPO in the liver and spleen of broilers were significantly increased by dietary AFB 1 , indicating that a low level of AFB 1 (22.5–25.0 μg/kg) could increase the oxidative status in the liver and spleen of broilers. Similar toxic effects of AFB 1 on oxidative status were observed in the liver and spleen of rats [32], and broilers [33,34]. …”
Section: Discussionmentioning
confidence: 55%